FAKTOR – FAKTOR YANG MEMPENGARUHI KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS MIJEN KOTA SEMARANG - Fajar; Sulistyani; Setiani, Onny (Jurnal Kesehatan Ibnu Sina (j-kis), 2019)
Pneumonia is still the biggest cause of childhood mortality and also the cause of death in many elderly people in the world. The incidence of Pneumonia in 2015 in Semarang City was found as many as 7,759 cases, an increase compared to the previous year which reached 4,295 cases. The problem of Penumonia disease is most prevalent in the Working Area of ​​Mijen Community Health Center, which is found 337 cases. This was a case-control study using the retrospective study method. Case group were 35 respondents and control group 35 respondents. The data analysis used univariate and bivariate analysis with Chi Square and the magnitude of risk with Odd Ratio and multivariate analysis to know the correlation (p) of independent variables together with dependent variable with logistic regression. The results of the research: 1) there is a relationship between the habit of opening the window of the house with the incidence of pneumonia (p = 0,031, OR = 3,273; 95% CI), 2) Cigarette Smoke Exposure (p = 0,002; OR = 5,537; 95% CI); 3) Healthy house (p = 0,010; OR = 6,303; 95% CI). Multivariate analysis results: 1). there is a relationship between the habit of opening the window of the house with the incidence of pneumonia OR = 3,596, 2). Cigarette Smoke Exposure OR = 8,426,3). House Condition OR = 9,240. The habit of opening the window of the house, exposure to cigarette smoke, and healthy homes have a relationship with the incidence of pneumonia